2020
DOI: 10.1016/j.jvoice.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Intonation in an a cappella Singing Quintet

Abstract: Tuning of each singer was closer to equal temperament than just intonation, but the size of major thirds was slightly closer to just intonation, and minor thirds closer to equal temperament. These findings were consistent within and between rehearsals, and across repetitions. Tuning was highlighted as an important feature of rehearsal during the study term, and a range of strategies were adopted to solve tuning related issues. This study provides a novel holistic assessment of tuning strategies within a singin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Only the rehearsal part of the sessions was analysed. Analyses of tuning and synchronisation in the performances have been reported in earlier publications ( D’Amario et al, 2020a , b ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Only the rehearsal part of the sessions was analysed. Analyses of tuning and synchronisation in the performances have been reported in earlier publications ( D’Amario et al, 2020a , b ).…”
Section: Methodsmentioning
confidence: 97%
“…For the second group, five sessions were pre-arranged by the researchers and recorded in a laboratory setting. Musical materials were provided in the form of two original pieces which were created for the purpose of the study (for details of the scores, see D ' Amario et al, 2020b). Neither piece had text, nor were sung to the vowel sound 'e' .…”
Section: Groupmentioning
confidence: 99%
“…Empirical research on choirs has revealed how singers strategically focus on intonation and control their use of vibrato to improve blend during rehearsals (D'Amario et al, 2020;Daffern, 2017). Timbral variations that affect blend have also been observed, including increases in high spectral energy (the so-called "singer's formant"; see Sundberg, 2018) that imbues the voice with an attractive ringing quality that is more typical in solo singing, and may thus reduce choral blend in certain contexts (Keller et al, 2017;Ternström, 2003;Rossing et al, 1987).…”
Section: Coordination Beyond the Temporal Dimension: Dynamics Intonat...mentioning
confidence: 99%
“…A realistic estimate of σ could start by considering that tunings in the database are usually measured to within 10 cents, but this is not the main source of variation. In humans, interval discrimination drops below about 100 cents [75][76][77][78], and humans typically sing with a standard deviation of at least about 10 -20 cents [10,69,[79][80][81][82][83][84]. Thus we can expect a reasonable upper bound to the fraction of significant results that can be detected of about 0.3 to 0.7.…”
Section: Tuning Variability Hinders Search For Universal Intervalsmentioning
confidence: 99%
“…Theory scales are ideal representations, but when performed they must exhibit some tuning variability. When this is studied, it typically contains questions of which ideal tuning system is intended -e.g., 12-TET or just intonation (JI) - [83,84,107] despite the fact that differences in intervals from different tuning systems are undetectable due to limits on singing stable pitchs and pitch perception [11]. In contrast, when discussing intonation in societies without theoretical scales, tuning variation is often highlighted as an intrinsic part of that culture [44,48,[108][109][110].…”
Section: How Different Are Scales?mentioning
confidence: 99%